Exploring the Process of Corporate Entrepreneurship : An Empirical Look at Individual Personality Factors and Entrepreneurial Behaviour from the Perspective of Middle Managers - Phua, Chun Meng (2013)
Corporate entrepreneurship has been a significant requirement for organisations in today’s fast paced market. There are opinions that perceive the urgency for organisation to breathe a culture of corporate innovation and entrepreneurial activity into the mindsets of executives as it is viewed not only of the organisation’s strategy but also as the focus of an organisation’s success (Kuratko et al., 2009). The profound impact of corporate entrepreneurship led us to research deeper to unfold new findings that would be beneficial for organisations to practice. With the intended strategy for organisation to be entrepreneurial, we observed the importance for key personnel to be aligned with the organisation’s vision. Compared to organisational factors, there is lack of reportage regarding personal factors, as information on this particular topic remains ambiguous.In the perspective of middle managers’ individual personality, the consequence of psychological ownership towards the improvement of entrepreneurial behaviour within the organisation is studied. Our research showed the significance of psychological ownership in fostering entrepreneurial behaviour in the perspective of middle managers to hold. The findings have added complexity in the corporate entrepreneurship process and implied that both organisational and personal factors are essential for organisations to consider in pursue of a higher entrepreneurial organisation. On the other hand, it would be another contribution to the context of literature regarding psychological ownership.We acknowledge our research is at the exploratory stage and suggest future researchers to develop the area of individual personality factors in corporate entrepreneurship, as the area of personal antecedents affecting corporate entrepreneurship still lacks depth and clarity. Importantly, the insights from this research would be able to assist organizations to more effectively promote the corporate entrepreneurship culture and strategise appropriately for the future success of the organization.